2013
DOI: 10.1111/xen.12030
|View full text |Cite
|
Sign up to set email alerts
|

The sweets standing at the borderline between allo‐ and xenotransplantation

Abstract: Animal cells are densely covered with glycoconjugates, such as N-glycan, O-glycan, and glycosphingolipids, which are important for various biological and immunological events at the cell surface and in the extracellular matrix. Endothelial α-Gal carbohydrate epitopes (Galα3Gal-R) expressed on porcine tissue or cell surfaces are such glycoconjugates and directly mediate hyperacute immunological rejection in pig-to-human xenotransplantation. Although researchers have been able to develop α1,3-galactosyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…have elegantly demonstrated production of Gal‐ and Neu5Gc‐deficient double‐knockout pigs using zinc finger nucleases, which elicit a significantly decreased in vitro antibody response compared to a Gal‐KO standard . Even with this progress, it is still recognized that the porcine glycome presents opportunities to generate more immunologically analogous porcine tissues . In addition to knocking out antigenic epitopes, the expression of human proteins, such as complement or coagulation regulatory factors, may improve engraftment and survival .…”
Section: Is There An Established Donor Islet Source?mentioning
confidence: 99%
“…have elegantly demonstrated production of Gal‐ and Neu5Gc‐deficient double‐knockout pigs using zinc finger nucleases, which elicit a significantly decreased in vitro antibody response compared to a Gal‐KO standard . Even with this progress, it is still recognized that the porcine glycome presents opportunities to generate more immunologically analogous porcine tissues . In addition to knocking out antigenic epitopes, the expression of human proteins, such as complement or coagulation regulatory factors, may improve engraftment and survival .…”
Section: Is There An Established Donor Islet Source?mentioning
confidence: 99%
“…Studies have shown that a-1,3-galactosyle (a-Gal) antigen in xenograft is one of the main target antigens in animal tissues and organs that cause acute rejection reaction after transplantation [8,9]. a-Gal is a kind of cell secreted glycoproteins or glycolipids that containing galactosamine core terminal residues, which exists as a cell surface molecule in most species, except humans and old world monkeys [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we describe the NSG/a-Gal null mouse, which is capable of engrafting human HSCs and can be used for preclinical evaluation of viral and tumor-based a-Gal epitope vaccines. In addition, it could be used in the xenotransplantation studies, in which the binding of anti-Gal Ab to the a-Gal epitope is the main cause of tissue rejection (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%